1991
DOI: 10.1007/bf02015628
|View full text |Cite
|
Sign up to set email alerts
|

Alexander's disease: Cranial MRI and ultrasound findings

Abstract: Cranial ultrasound (US) findings and magnetic resonance imaging (MRI) are presented in an infant with Alexander's disease. Both methods may help the clinician with the early diagnosis of this rare disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In two-thirds of the cases, the abnormal white matter had a slightly swollen appearance. The distribution and appearance of white matter abnormalities were compatible with the diagnosis of Alexander disease (22)(23)(24)(25)(26). Generally, the demonstration of Rosenthal fibers in brain tissue is considered a prerequisite to a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In two-thirds of the cases, the abnormal white matter had a slightly swollen appearance. The distribution and appearance of white matter abnormalities were compatible with the diagnosis of Alexander disease (22)(23)(24)(25)(26). Generally, the demonstration of Rosenthal fibers in brain tissue is considered a prerequisite to a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to the white matter changes, all patients had basal nuclei abnormalities, which were either changes in signal intensity and some swelling (Fig 4) or marked atrophy (Fig 5). To our knowledge, the involvement of the basal nuclei in Alexander disease is not described in the MR imaging literature (22)(23)(24)(25)(26), but from histopathologic analysis, it is known that the basal nuclei contain a relatively high volume of Rosenthal fibers (27)(28)(29). It is also known that in Alexander disease, the course of the white matter abnormalities is characterized by an increase in volume followed by cystic degeneration and a loss of volume (29,30).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Four of five criteria must be met for MRIbased diagnosis [9]. Valk et al suggested that MRI criteria for AD include spread of disease from frontal lobes in a rostrocaudal direction, preserved occipital lobes and genu of corpus callosum, involvement of arcuate fibers, and lack of involvement of the cerebellum and brain stem [10,11]. The predominant involvement of the frontal white matter on MRI and the macrocephaly are findings that have been noted in all infants and children diagnosed with AD [6,8,9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since it was fi rst described in 1949 [1] , the diagnosis has been based on histopathological fi ndings in autopsy or brain biopsy, especially the demonstration of Rosenthal fi bres [9] . Typical fi ndings in cerebral imaging include leukencephalopathy with frontal predominance and degenerative changes of the basal ganglia [2,11,22,26] . Magnetic resonance criteria for the diagnosis of Alexander disease have been established [25] .…”
Section: Introductionmentioning
confidence: 99%